Uji Coba Evaluasi Kinerja di PT Nikomas Gemilang Bagian Assembling Menggunakan Model Evaluasi Critical Incident - Rizkiyah Nurmalia; Tuti Alawiyah; Syamsul Hidayat (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to evaluate performance at PT Nikomas Gemilang, one of the largest footwear manufacturers in Indonesia, using Critical Incident Technique (CIT). This method is used to identify critical incidents that have a significant impact on the success or failure of the company's operations. Data was obtained through in-depth interviews, direct observation, and document analysis such as performance and work incident reports.The results showed that the most frequent critical incidents included production errors (40%), logistics delays (27%), and work accidents (20%). The main causes include a lack of technical training, weak coordination between departments, and minimal attention to safety standards. These incidents negatively impacted the company's productivity, product quality, and operational efficiency.Through the implementation of CIT, PT Nikomas Gemilang was able to identify the root causes of the problem and develop strategic measures, such as employee training programs, strengthening coordination with ERP technology, and improving work safety standards. With this data-driven evaluation, the company is expected to reduce the risk of similar incidents in the future, improve operational efficiency, and maintain competitiveness in the global market.